2009
DOI: 10.1017/s0007114509992467
|View full text |Cite
|
Sign up to set email alerts
|

The combined impact of plant-derived dietary ingredients and acute stress on the intestinal arachidonic acid cascade in Atlantic salmon (Salmo salar)

Abstract: Havforskningsinstituttets institusjonelle arkiv Brage IMR - Institutional repository of the Institute of Marine Research b r a g e i m rDette er forfatters siste versjon av den fagfellevurderte artikkelen, vanligvis omtalt som postprint. I Brage IMR er denne artikkelen ikke publisert med forlagets layout fordi forlaget ikke tillater dette. Du finner lenke til forlagets versjon i Brage-posten. Det anbefales at referanser til artikkelen hentes fra forlagets side. Ved lenking til artikkelen skal det lenkes til po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
32
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 52 publications
(42 citation statements)
references
References 59 publications
8
32
2
Order By: Relevance
“…For cox2a and in particular cox2b however, we observed a very low expression in anterior enterocytes compared to posterior enterocytes. This agrees previous notions in Atlantic salmon cox2a (Oxley et al 2010), and may be linked to, in part, ion regulation and water absorption. In rats, PGE 2 will reduce water and chloride absorption (Hodeify and Kreydiyyeh 2007).…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…For cox2a and in particular cox2b however, we observed a very low expression in anterior enterocytes compared to posterior enterocytes. This agrees previous notions in Atlantic salmon cox2a (Oxley et al 2010), and may be linked to, in part, ion regulation and water absorption. In rats, PGE 2 will reduce water and chloride absorption (Hodeify and Kreydiyyeh 2007).…”
Section: Discussionsupporting
confidence: 92%
“…Whereas the expression was detected to be highest in the gill and at a similar lower level in muscle, midgut and hindgut, while the expression was subsequently lower in spleen and kidney and not detected in the liver. Previous studies have reported expressional differences between midgut and hindgut for cox2a (Oxley et al 2010), we could not detect any differences in expression of the cox genes between hindgut and midgut. However in our preparation we had used the whole intestine including muscle and enterocytes.…”
Section: Gene Expression In Different Tissuescontrasting
confidence: 90%
See 3 more Smart Citations